(3Gdedd hGdfMds - (3eMeO Hf YHO GdcQje Hf CMeO GdTgQSJGfj,J (B548 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf HLejY eMGeOg cdgG Ydi LejY fYeGFg s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA GdcdGe Ydi BQGA (B" (3aQahQjhS s
(3HChd GdfSNI agQS GdehVhYGJ GdcJGHs
(3HBNQgG JcedI HNW MOjK hai CKfGA gPg GdJcedI NQes
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3GdJhMjO hGdedd hGdfMds